Anatomist and Co-Founder of Polish Veterinary Education-Ludwik Henryk Bojanus (1776-1827) - Jarosław Sobolewski; Maciej Zdun (MDPI AG, 2023)
Ludwig Henry Bojanus was born on 16 July 1776 in Buchsweiler, Alsace. After studying in Jena and Vienna, L. H. Bojanus enrolled at the University of Jena for his doctoral studies. Bojanus's scientific activities are closely associated with Vilnius, where he was a professor of veterinary medicine from 1806 (he was elected to this position in 1804). In 1815, he became a professor of comparative anatomy. These were the times of the greatest flourishing of Vilnius University, where the foundations of modern Polish science were being laid. At Vilnius University, he established a technical and anatomical-pathological office for the zoo, a veterinary clinic and a model forge for shoeing horses in 1823. Bojanus founded a veterinary school in Vilnius and drew up a plan for a veterinary institute, which was not opened until 1832, simultaneously with the opening of the medico-surgical academy. He became known as one of Europe's most prominent anatomists and zoologists. A lasting memorial to the scientist is the monograph "Anatomy of the Tortoise", which many scholars still point to today as a model of accurate and precise anatomical research. He was the first to identify the anatomical differences between the European bison (Bos bonasus) and the aurochs (Bos primigenius). In his lectures on comparative anatomy, Bojanus presented the principle of uninterrupted development. He can be described as one of the most decisive and consistent evolutionists before Darwin. He died in 1827.